Special workThe genetic diagnostics of primary cutaneous T-cell lymphomas. Part II: The role of chromosomal aberrations in diagnostics and pathogenesis of primary cutaneous T-cell lymphomas - Nedoszytko, Bogusław; Sokołowska-Wojdyło, Małgorzata; Zabłotna, Monika; Gleń, Jolanta; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
. Primary cutaneous T-cell lymphomas (CTCL) are a heterogeneous group of neoplasms, from which mycosis fungoides (MF) and Sezary syndrome (SS) are the most frequently observed. The aetiology of CTCL is still unknown. The most probable factors involved in CTCL pathogenesis are chronic response to antigens (chemicals, viruses, bacteria), smoking and chronic exposure to UV causing gene and chromosome mutations and consequently establishing genomic instability phenotype. Cases of MF/SS diagnosis dominate among published results of cytogenetic analysis of CTCL. Chromosomal aberrations are observed mostly in advanced stages of disease and precede disease progression. No specific, recurrent chromosomal aberrations were found for this type of neoplasms. The karyotypes of examined lymphomas are mostly complex with many different structural and numerical aberrations. The most frequently observed changes are loss of genetic material of chromosomes 1p, 2p, 6q, 9p, 10q, 12q, 13q and 17p, which result in loss of several tumor suppressor genes located in these regions like CDKN2A (9p), PTEN (10q), RB1 (13q), TP53 (17p) and newly described gene NAV3 (12q). It was described that chromosomal aberrations may cause many other molecular changes like oncogene activation, transcription factor disregulation, cell cycle aberration, DNA reparation and apoptosis process disregulation.